The assessment of the correlation between the levels of toxic metals, cadmium and lead, and the concentration of steroid hormones in ovarian tissue homogenates obtained from postmenopausal women - Brodowska, Agnieszka; Brodowski, Jacek; Karakiewicz, Beata; Starczewski, Andrzej; Laszczyńska, Maria; Sałacka, Anna; Kulig, Jolanta (Menopause Review/Przegląd Menopauzalny, 2009)
Introduction: Environmental factors have an essential impact on the time of menopause. The aim of this study was to assess the correlation between the levels of cadmium (Cd) and lead (Pb) and the concentrations of oestradiol, testosterone and androstenedione in ovarian homogenates depending on the time from the last menstrual bleeding (LM). Material and methods: The study involved 39 postmenopausal women who had not used substitutive hormone therapy before, and whose ovaries had been removed during elective surgery. Two groups of women were analyzed, namely group A composed of 20 women being no more than 5 years after LM, and group B consisting of 19 women more than 5 years after their last menstrual period. The levels of cadmium and lead in ovarian homogenates were measured using emission spectrometry, while the concentrations of oestradiol (E2), testosterone (T) and androstenedione (A) were determined by ELISA method. Results: The mean lead concentration in ovarian homogenates was 9.85 ±4.2 µg/kg, and the mean level of cadmium 3.52 ±1.7 µg/kg. A significant positive correlation was found between the level of cadmium in ovarian homogenates and the age of the women examined (rs = 0.37). No differences were found in the concentrations of cadmium and lead in ovarian homogenates depending on the time elapsed from the last menstruation (group A vs. group B). The mean E2 concentration in homogenates was 31.84 ±12.5 pg/mg protein, testosterone 0.21 pg/mg protein, and androstenedione 0.56 pg/mg protein. No correlation was found between the levels of Pb and Cd and the concentrations of the tested steroid hormones in ovarian homogenates. However, significantly higher levels of E2 and androstenedione were observed in ovarian homogenates obtained from group A women. Conclusions: The lack of substantial differences in the concentrations of cadmium and lead in ovarian homogenates depending on the time elapsed from the last menstruation, and especially no significant correlations between Cd and Pb and the steroid hormones analyzed, may suggest that these elements have no influence on the time of the last menstrual bleeding.